ANALISIS PENGGUNAAN SISTEM INFORMASI GEOGRAFIS (GIS) DALAM PERENCANAAN TRANSPORTASI DI KOTA PADANG - Nina Ismayani; Fatma Azahra; Sanika Sapolaga (Universitas Tamansiswa Padang, 2025)
Effective transportation planning is one of the key factors in supporting community mobility and sustainable regional development. Padang City, as the capital of West Sumatra Province, has experienced significant regional growth and an increasing number of vehicles, thus requiring innovative approaches in transportation planning. This study aims to analyze the utilization of Geographic Information Systems (GIS) in the transportation planning process in Padang City. The research method used was a descriptive qualitative approach. Primary data were obtained through in-depth interviews with related institutions, such as the Transportation Agency and the Regional Development Planning Agency (Bappeda) of Padang City, while secondary data were collected from planning documents, scientific publications, and related spatial data. The collected data were analyzed using content analysis techniques for qualitative data and spatial analysis for map-based data using GIS software such as ArcGIS and QGIS. The results showed that GIS provides significant contributions in identifying traffic patterns, congestion points, and transportation infrastructure needs. GIS also facilitates thematic map creation and future transportation scenario simulations. However, GIS implementation still faces challenges, including limited spatial data, human resource capacity, and suboptimal cross-sector coordination. Therefore, strategic measures are needed to strengthen institutional capacity, provide integrated spatial data, and encourage policies that support GIS utilization in transportation planning. Thus, GIS can be optimized to create an efficient, responsive, and sustainable transportation system in Padang City.